Is Minimal Change Disease Associated with Prostate Cancer or Is Age Just a Number? - Patrícia Kleinová; Matej Vnučák; Karol Graňák; Monika Beliančinová; Tímea Blichová; Ivana Dedinská (Reports, 2024)
Background: Prostate cancer is the most common malignancy in men. Secondary nephrotic syndrome, a feature of paraneoplastic syndrome, occurs in 11% of cases and is mainly caused by membranous glomerulopathy. The association between minimal change disease and prostate cancer is rare. Only one cause has been described in the available literature. Case presentation: We present the case of a 77-year-old patient who was admitted to our department with stage 3 acute kidney injury and with nephrotic syndrome with anasarca (creatinine: 168 µmol/L, eGFR: 33 mL/min/1.73 m2, albumin: 18.5 g/L, total cholesterol: 6.86 mmol/L, urine albumin creatinine ratio: 812.7 mg/mmol). In the differential diagnosis of nephrotic syndrome, looking for a secondary cause is essential, so the parainfectious causes of nephrotic syndrome were excluded. An elevated prostate-specific antigen (10.69 ng/L) was found when screening for oncological causes, and prostate adenocarcinoma was identified on biopsy. A renal biopsy was then performed with a finding of minimal change disease. Despite the generally accepted guidelines of prostate carcinoma in that stage and age of the patient being watchful waiting, antiandrogen therapy was started with the cooperation of a urologist. There was a significant improvement in renal parameters in the patient (creatinine: 87 µmol/L, eGFR: 73 mL/min/1.73 m2, albumin: 33.4 g/L, urine albumin creatinine ratio: 27.6 mg/mmol). Conclusion: This case shows the importance of multidisciplinary cooperation in the treatment of secondary causes of nephrotic syndrome. In the case of proven paraneoplastic syndrome, it is necessary to start treating the malignancy; however, in general, a conservative approach without treatment is recommended.